Advances in Wearable Strain Sensors Based on Electrospun Fibers. (25th February 2023) - Gao, Zhiyuan; Xiao, Xiao; Carlo, Aiden Di; Yin, Junyi; Wang, Yanxin; Huang, Linjun; Tang, Jianguo; Chen, Jun
Abstract: Wearable strain sensors with the ability of detecting physiological activities play an important role in personalized healthcare. Electrospun fibers have become a popular building block for wearable strain sensors due to their excellent mechanical properties, breathability, and light weight. In this review, the structure and preparation process of electrospun fibers and the conductive layer are systematically introduced. The impact of materials and structures of electrospun fibers on the wearable strain sensors with a following discussion of sensing performance optimization strategies is outlined. Furthermore, the applications of electrospun fiber‐based wearable strain sensors in biomonitoring, motion detection, and human‐machine interaction are presented. Finally, the challenges and promising future directions for the community of wearable strain sensors based on electrospun fibers are pointed out. Abstract : In this review, the materials usage and preparation process of electrospun fibers are systematically introduced for constructing wearable strain sensors with applications in biomonitoring, motion detection, and human‐machine interaction. The challenges and promising future directions are also pointed out to advance the frontier of wearable strain sensors based on electrospun fibers.